ANALISIS KINERJA KEUANGAN PADA KOPERASI PRIMA UMEGA KOTA PEKANBARU - Mifturahmah, Ririn; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to know and analyze the financial performance standards of the liquidity ratio, solvency, activity and profitability of the cooperative trade and services Prima Umega Pekanbaru city during the period of 2014-2018.This research uses secondary data in the form of data obtained by authors through, manual report and financial statements of trade cooperatives and services Prima Umega Kota Pekanbaru as required researchers for the analysis of liquidity, solvency, activity and profitability.The results of the analysis showed that the financial statements of trade cooperatives and services of Prima Umega 2014-2018 period based on the liquidity Ratio, solvency, activity and profitability are: 1) The liquidity ratio analysis, current Ratio gets the predicate "bad", and at the cash Ratio got the predicate "bad"; 2) analysis of the solvency ratio, debt to total assets ratio received a "very good" predicate, and debt to equity ratio received a "good" predicate; 3) Activity ratio analysis, total assets turnover ratio gets "bad" predicate;Analysis of the activity ratio, the total assets turnover ratio received a predicate "Bad" and the working capital turnover ratio received a predicate "Bad"; 4) The analysis of the profitability ratio, return on asset gets the predicate "good enough", return on equity gets the predicate "less good" and Net Proft Margin gets the predicate "very good". Keyword : Financial Performance, Liquidity, Solvency, Activity, and Profitability.